The Effect of Market Orientation and Entrepreneurship Orientation on Marketing Performance Mediated Product Innovation in Bead MSMEs (International Conference of Graduate School on Sustainability (ICGSS), 2021)
This research was motivated by a decline in sales at the MSME beads in Plumbon Gambang Village. The purpose of this study was to determine the effect of market orientation and entrepreneurial orientation on product innovation, the effect of product innovation on marketing performance, the effect of market orientation on marketing performance, the effect of entrepreneurial orientation on marketing performance, the effect of market orientation on marketing performance by mediating product innovation and the effect of entrepreneurial orientation. on marketing performance by mediating product innovation. This study uses a quantitative approach. The sample of this study was 43 MSME beads in Plumbon Gambang Village in 2018 with a total sampling technique. The research instrument used a questionnaire and analyzed using SEM-PLS analysis. The results of this study indicate that market orientation has a significant effect on product innovation, entrepreneurial orientation has a significant influence on product innovation, product innovation has a significant effect on marketing performance, market orientation does not have a significant effect on marketing performance, entrepreneurial orientation does not have a significant impact on product innovation. significant influence on marketing performance, product innovation can mediate market orientation on marketing performance and product innovation can mediate entrepreneurial orientation on marketing performance